Nutrition and diet therapy : principles and practice - DeBruyne, Linda Kelly; Pinna, Kathryn ;Whitney, Ellie (Pacific Grove, California : Brooks/Cole Publishing Company, 2010)
Organized by diets, this book helps you to learn the skills needed to be successful in your career in nutrition care. It provides core nutrition concepts and clinical content...
Part one: Basic nutrition -- Part two: Nutrition throughout life -- Part three: Nutrition in heealth care -- Part four: Medical nutrition therapy
Includes index.
Keywords: DIET THERAPY